1986
DOI: 10.1007/bf00310637
|View full text |Cite
|
Sign up to set email alerts
|

Possible mediation of catecholaminergic pathways in the antinociceptive effect of an extract of Cannabis sativa L.

Abstract: An extract of cannabis (5 and 15 mg/kg expressed as delta 9-THC) orally administered to rats caused an elevation of the nociceptive threshold (tail-flick latency and vocalization tests). Naloxone and naltrexone (blockers of mu-type opiate receptors) as well as MR 1452 (blocker of kappa opiate receptors) did not prevent the antinociceptive effect of cannabis when used at the dose of 2 mg/kg SC; only a high dose (10 mg/kg SC) of these narcotic antagonists partially blocked cannabis antinociception. ICI 154, 129,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These findings provide a strong basis for the conclusion that the actions of WIN 55,212-2 on pain and movement are mediated by separate processes and suggest that the decreased behavioral responsiveness to noxious stimuli does not result merely from a disruption of motor function. This conclusion is supported by studies that demonstrated antinociceptive actions of cannabinoids in a test (vocalization to shock) that does not require a gross motor response (Ferri et al, 1981(Ferri et al, , 1986.…”
Section: Discussionmentioning
confidence: 88%
“…These findings provide a strong basis for the conclusion that the actions of WIN 55,212-2 on pain and movement are mediated by separate processes and suggest that the decreased behavioral responsiveness to noxious stimuli does not result merely from a disruption of motor function. This conclusion is supported by studies that demonstrated antinociceptive actions of cannabinoids in a test (vocalization to shock) that does not require a gross motor response (Ferri et al, 1981(Ferri et al, , 1986.…”
Section: Discussionmentioning
confidence: 88%
“…28,29 Relation of cannabinoids to dopaminergic neurotransmitters Six-hydroxydopamine produces degeneration in catecholamine terminals that block THC antinociception effects. 30 Cannabimimetic agents cause ''inhibition of the dopaminergic nigrostriatal system.'' 31 Cannabinoid receptors are colocalized with dopamine D 1 receptors on striatonigral dynorphin/substance-P-containing neurones and with dopamine D 2 -receptors on striatopallidal enkephalinergic neurons.…”
Section: The Cannabinoid Receptor Systemmentioning
confidence: 99%